Hypertension Patients’ Adherence in Chronic Disease Care Program at Public Health Center - Zyuli Sholikatin, Wahyuni; Dwi Wahyuni, Erna; Diyan Rachmawati, Praba (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension has a significant role in hypertension management. The hypertension control program can be performed through four Prolanis (chronic disease management program) programs and four hypertension management obedience programs. Objective: Explaining the correlation between the patients’ obedience following Prolanis and the patients’ hypertension. Method: This study employed a quantitative design with the correlation method. The respondents were twenty-four hypertension Prolanis participants, with total population sampling method. The dependent variables were Prolanis and patients’ obedience to join Prolanis. The independent variable was hypertension. The data were collected by using special data, a dietary compliance questionnaire, physical activity (Baecke), medication (MMA-8) and medical records. The statistic test employed Chi-square with Fisher exact as an alternative test with a significant value of less than 0.05. Result: There was a correlation between Prolanis implementation and hypertension patients’ obedience. Conclusion: Half of the patients are obedient in implementing Prolanis.Therefore, the obedient patients and the disobedient patients are of equal numbers. There is a significant correlation between Prolanis implementation and patients with hypertension. The patients’ compliance in implementing Prolanis and blood pressure in patients with hypertension have a significant correlation. The assessment of the four patient obediences in implementing Prolanis in hypertension needs to be performed, considering the importance of maintaining normal blood pressure and preventing the complications.